The adsorption of methylene blue dyes from aqueous solution on biochar prepared from banana peel: article - Khasri, Azroy Ezetty; Alias, Rusmi (2019)
Dyes is a synthetic origin with complex aromatic molecular structures that make them more stable and difficult to biodegrade. The discharge of colored wastewater from these industries into natural streams has caused many major problems. Although methylene blue is not highly dangerous, some harmful effects can be caused. Banana plants are grown in over 130 countries causing a large number of banana skins are wasted each year. Therefore, the adsorption of methylene blue (MB) dye onto banana peel biochar (BPB) were investigated in a batch process. Different analytical techniques such as TGA and FTIR have been used to characterize this BPB. The parameter studied in this work were: adsorbent dosage [0.05-2.0g], initial dye concentration [25-250mg/L] with contact time of 24 hours. The optimum adsorption of MB was at 2.0 adsorbent dosage with 91.79 percent removal, which is the percentage of MB increased with an increase in adsorbent dose and also an increase in adsorbed amount of MB with an increase in initial MB concentration. The uptake of adsorption increased at the initial stage with time and slowed down before attaining the equilibrium. At 250 mg/L, the adsorption uptake reaches 176.94 mg/g with contact time of 24 hours. The isotherm data obtained for MB dye was best fitted with the value R2= 0.9991 by Freundlich model.